Structural basis of thymidine-rich DNA recognition by Drosophila P75 PWWP domain. - Jin, Z.; Meng, Z.; Liu, Y.; Li, C.; Zhang, X.; Yin, Y.; Gao, G.; Dou, K.; Huang, Y. (Communications biology, 2025)
Drosophila P75 (dP75), a homolog of the human LEDGF/p75, is crucial for oogenesis by recruiting the histone kinase Jil-1 to euchromatin and impeding H3K9me2 spreading. Like LEDGF, dP75 binds transcriptionally active chromatin, but its precise mechanism remains unclear. Here we show that its PWWP domain prefers binding to thymidine-rich DNA over GC-rich sequences. Crystal structures both in apo and ssDNA-bound states, reveal a domain-swapped homodimer. The aromatic cage, known to recognize histone methyllysine, also engages thymine. Mutations in this cage mimic dP75 knockout phenotypes, including impaired chromatin binding, transposon upregulation, and female sterility. Although dP75 maintains chromatin-bound in H3K36A mutant flies, alterations in the aromatic cage disrupt this localization, underscoring its role in DNA binding. These findings reveal how dP75 targets euchromatin through a PWWP domain that integrates histone reading and nucleotide recognition, advancing our understanding of PWWP domains.